FREQUENCY OF CANINE NEOPLASIAS IN LIMA: RETROSPECTIVE STUDY IN THE PERIOD OF 1995-2006 - de Vivero C., Luis E. (2013)
Canine histopathological records from de Pathology Laboratory of the Universidad Nacional Mayor de San Marcos, Lima, during the period of 1995-2006 were evaluated for determining the frequency of neoplasias in relation to sex, age, breed, cellular origin, and localization. Out of 4438 canine records, 1092 corresponded to neoplasia (24.6%). Higher tumoral frequency was found in age groups of 5 to <9 (37.1%) and ≥9 (35.6%) years old. None differences were found due to sex, but the Boxer breed was the most affected (12.1%). Malignant neoplasias were most frequent (64.9%) than benign ones, where the transmissible venereal tumor was the most frequent benign tumor and the mammary adenocarcinoma was the most frequent malign tumor. Skin and subcutaneous tissue (39.5%) and mammary gland (16.7%) were the most common sites for neoplasias.